Nest Locations for the Kittlitz Murrelet - Jonathan J Felis; Michelle L Kissling; Robb SA Kaler; Leah A Kenney; Matthew J Lawonn (USGS Science Data Catalog, 2016)
A compilation of all known nest records and locations to identify landscape-scale parameters (distance to coast, elevation, slope, and land cover) that provide potential nesting habitat in four regions: northern Alaska, Aleutian Islands, Alaska Peninsula Mountains and Kodiak Island, and Pacific Coastal Mountains (including nearshore interior Canada).